2011
DOI: 10.1159/000327141
|View full text |Cite
|
Sign up to set email alerts
|

An Emerging Role for Understanding Orthostatic Hyp‘er’tension in the Cardiorenal Syndrome

Abstract: Orthostatic hypertension (OHT) is a clinically important problem increasingly recognized in persons with borderline hypertension, diabetes mellitus, and autonomic neuropathies, and in the elderly. Moreover, the association of OHT with progression of target end-organ damage, especially coronary heart disease and chronic kidney disease (CKD), and the attendant increased cardiovascular disease (CVD) and CKD risk, is gaining attention but is still underappreciated. There are various mechanisms that contribute to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 86 publications
0
10
2
Order By: Relevance
“…OH was defined as a decline in SBP of at least 20 mm Hg and/or a decline in DBP of at least 10 mm Hg after either 0 or 2 minutes from a supine to an upright posture . The definition of OHT was a postural increase of at least 20 mm Hg in the orthostatic SBP change . Participants with neither of these two patterns were classified into an orthostatic normotension (ONT) group.…”
Section: Methodsmentioning
confidence: 99%
“…OH was defined as a decline in SBP of at least 20 mm Hg and/or a decline in DBP of at least 10 mm Hg after either 0 or 2 minutes from a supine to an upright posture . The definition of OHT was a postural increase of at least 20 mm Hg in the orthostatic SBP change . Participants with neither of these two patterns were classified into an orthostatic normotension (ONT) group.…”
Section: Methodsmentioning
confidence: 99%
“…Orthostatic hypertension may develop in cases of reduced renal blood flow during standing. This particular condition has been observed in patients with nephroptosis, a clinical entity characterized by increased mobility of the kidneys and defined as significant descend of the kidney (by at least 5 cm or two vertebral bodies on intravenous urography) when standing . Descend of the kidney can cause stretching and torsion of the renal artery, reduction of renal blood flow and, consequently, OHT .…”
Section: Pathophysiologymentioning
confidence: 97%
“…Moreover, Vriz et al observed that OHT patients had higher resting cardiac output and heart rate, as well as higher urinary norepinephrine output compared with non‐OHT individuals, suggesting that OHT is characterized by increased baseline sympathetic activity, and the orthostasis‐induced cardiac output reduction may trigger sympathetic over‐response . ANS dysfunction is attributed to impaired arterial and cardiopulmonary baroreceptors’ sensitivity and/or baroreflex failure to adjust to “normal” BP values, while alpha‐adrenergic vascular hyperactivity is believed to be another important mechanism mediating the excessive vasoconstriction . Activation of the renin‐angiotensin‐aldosterone system (RAAS) and increased vasopressin secretion may also be involved in the development of OHT .…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Orthostatic hypotension is also an established marker for cardiovascular risk in patients with hypertension [ 3 , 4 ], in the elderly [ 5 8 ] and in the general population [ 9 12 ]. Considerably less is known, however, about the prevalence and clinical impact of the reverse phenomenon, orthostatic hypertension, which implies an exaggerated rise in blood pressure when assuming an upright position [ 13 , 14 ]. Orthostatic hypertension has been associated with increased prevalence of silent cerebrovascular lesions in the elderly [ 15 ], and with increased risk for incident lacunar strokes in the general population [ 16 ].…”
Section: Introductionmentioning
confidence: 99%